Anuran communities in different riparian habitats: Native forest, secondary forest, and sugarcane - Baldi, Ludmila Cristina; Santos, Fernanda Bastos Dos; Esteves, Katharina Eichbaum; Ferreira, Fábio Cop [UNESP]; Rocha, Mariane Targino; Santana, Juliana Macedo; Teixeira, Patrícia Coelho; Ferreira, Cláudia Maris (Brazilian Herpetological Society, 2015)
This study aimed to test the influence of different riparian habitats on the structure of anuran communities in southeastern Brazil. Nine stream stretches were selected representing three different riparian habitat types: Native Forest, Secondary Forest, and Sugar-cane. A total of 223 individuals of 17 species and five families were captured. The Chao1 richness index indicated that after standardizing the sampling effort the Native Forest sites had higher richness than the Secondary Forests and Sugarcane sites, which presented similar richness. The Abundance and Biomass Curves for the Native Forest sites showed an overlap of the weight and abundance curves, suggesting that these sites presented lower disturbance levels. A disturbance gradient from Native Forest towards Sugarcane sites was observed. The Bray-Curtis similarity index showed a significant effect of riparian condition on species composition. Our results suggest that Sugarcane and Secondary Forest sites limit the distribution of certain species, such as those from the family Hylidae species related to litterfall, and enable colonization by open-habitat species that are capable of resisting anthropic pressure.
Keywords: Agriculture; Amphibians; Fragmentation; Monoculture